Silurichthys exortivus, a new catfish (Teleostei: Siluridae) from eastern Borneo, Indonesia - Ng, Heok Hee; Kottelat, Maurice (Zootaxa, 2022)
Silurichthys exortivus, a new species of silurid catfish, is described from the Mahakam River drainage in eastern Borneo. The new species can be distinguished from congeners in lacking a dorsal fin, having 4 (vs. 6–7) principal rays on the upper caudal-fin lobe and a combination of: body depth at anus 14.0% SL, caudal peduncle depth 5.1% SL, pelvic fins absent, 54 anal-fin rays, caudal fin with asymmetrical lobes (upper lobe 1.1 times longer than lower), 48 vertebrae, 1 gill raker on the first branchial arch, and a mottled brown body. Based on the reduced number of principal caudal-fin rays, S. exortivus, S. ligneolus and S. sanguineus are hypothesized to form an exclusively Bornean clade.